Corporate Credibility Assessment: The Perception of Chinese Malaysian - Irma Yazreen, Md Yusoff; Soetrisno, Fathan; Dayang Affizzah, Awang Marikan; Hin, L. K. (Human Resource Management Academic Research Society, 2020)
The purpose of this research is to examine the perception of Chinese Malaysian towards corporate credibility. Online questionnaire was created and distributed to collect primary data from the target respondents who are Malaysian with Chinese descendant residing in Penang. 250 online questionnaires were collected and analysed through the use of Statistical Package for Social Sciences (SPSS) for the tabulation of respondents’ demographic profile and Structural Equation Modelling –Partial Least Square (SEM –PLS) to analyse the relationship between the variables. Based on the hypothesis testing, the results show that customer focus, product quality, expertise and trustworthiness has significant influence on the perception towards organization credibility, while transparency has no significant influence on the perception of Penang Malaysian Chinese towards organization credibility.